Educational Background Factors on Motor Vehicle Accident; Analysis Using a Structural Equation Modeling - Pada Lumba (Aptek, 2026)
This research focuses on the impact of human, road and environmental as well as vehicles factors on the risk of accidents in driver of motor vehicle. The study is located in Indonesia. The data were collected by distributing questionnaires through social media. The number of respondents in this study consist of 260 drivers of motor vehicle with 87 respondents from senior high school (SMA) educated and below, 100 respondents from undergraduate (S1) educated and 73 respondents from postgraduate (S2) educated. The data were analyzed using Structural Equation Modeling (SEM). Key finding in this study related to indicator of latent variable is driver experience. All group (SMA, S1 and S2) in this study show indicated that driver experience indicator influence the latent variables driving performance and latent variables risky driving behavior. In addition to, the smaller value of R square of the model, the higher educational background of motor vehicle drivers. This shows that there is a relationship between the educational background of drivers and the road accidents occurance. Meaning that the higher educational background of drivers, the smaller the risk of road accidents occurance of drivers.